Chain extension of polyamide 6 using multifunctional chain extenders and reactive extrusion for melt foaming. (November 2017) - Xu, Menglong; Yan, Haichao; He, Quanjin; Wan, Chen; Liu, Tao; Zhao, Ling; Park, Chul B.
Graphical abstract: Highlights: High melt strength PA6 was prepared by reactive extrusion with chain extenders. High non-isothermal crystallization rates in the modified PA6 under high CO2 . The high crystallization rate seemed to be related to the small cell diameters in the PA6′s foams. Abstract: We used the reactive extrusion method to modify virgin polyamides 6 (PA6) for melt foaming. The reactive extrusion was performed with a Haake melt mixer, and the following modifiers were used: 1, 1′-isophthaloyl-bis-caprolactam (IBC), 2, 2′-bis(2-oxazoline) (BOZ) and an epoxy-type chain extender KL-E4370 (EP) as well as an IBC and BOZ combination. The chain extender's effects on the reactive modification were characterized through the PA6 chain's rheological properties, including the storage modulus, the loss modulus, and the dynamic complex viscosity. The EP-modified PA6 was shown to have the highest viscoelasticity; that is, the highest melt strength. The PA6′s melting and crystallization properties were also investigated. A high-pressure differential scanning calorimeter (DSC) under compressed CO2 was used to evaluate the foaming temperature windows. Finally, the foamability of the modified PA6 was verified by our batch melt foaming experiments, where supercritical CO2 was used as the blowing agent. The EP-modified PA6 with the highest melt strength had the widest foaming window and the biggest expansion ratio.